XI. No. 2. April 2019 JURNAL TEPAK MANAJEMEN BISNIS 258 PERAN KUALITAS PRODUK, CITRA MEREK, DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DAN LOYALITAS MEREK PADA PENGGUNA SMARTPHONE MEREK APPLE DI KOTA PEKANBARU - Setiawan, Hanang Yus; Alwie, Alvi Furwanti (Jurnal Tepak Manajemen Bisnis, 2019)
This study aims to determine the Role of Product Quality, Brand Imageand Lifestyle on Purchasing Decisions and Brand Loyalty in Apple BrandSmartphone Users in Pekanbaru City. This study uses primary data, namely dataobtained from interviews and questionnaires to consumers who have purchasedApple Brand Smartphones. Secondary data obtained relates to the literaturerelating to researchers. The sample in this study was 270 consumers, taken bypurposive sampling method. The analytical method used in this study is to use theStructural Equation Model (SEM) analysis with the help of the AMOS program.The results of the study show that 1) Product quality has a positive andsignificant effect on purchasing decisions. 2) Brand image has a positive andsignificant effect on purchasing decisions. 3) Lifestyle has a positive andsignificant effect on purchasing decisions, and 4) Purchasing decisions have a positive and significant effect on brand loyalty